Evaluasi Pengelolaan Keuangan Desa di Desa Dumati Kecamatan Telaga Biru - Herlina Pakaya; Sahmin Noholo; Lukman Pakaya (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aimed to evaluate village financial management in Dumati Village, Telaga Biru Subdistrict, based on the principles of transparency, accountability, participation, orderliness, and budgetary discipline. The research employed a descriptive approach, where the data analysis technique used was qualitative analysis. The data collection techniques used were interviews and documentation. Thus, in reference to the results of the interviews and documentation, they were compared using indicators in accordance with the Ministry of Home Affairs No. 20 of 2018. The research findings revealed that the Dumati Village government's financial management adheres to Pemdagri No. 20 of 2018, which mandates transparent, accountable, participatory, orderly, and disciplined budgets that meet all indicators. Also, the management was very effective, so it was sufficient and beneficial for the community.